ANALISIS PERBEDAAN MOTIVASI DAN PARTISIPASI WARGA BELAJAR DI PKBM DESA DAN KOTA: STUDI KASUS PKBM LASKAR PELANGI DAN PKBM AL-IKHRAM - Ibnu Hajar; Anifah; Cindi Kezia Simbolon; Rachel Nadia S. B. Banjarnahor; Sentia Br. Malau; Muhammad Sa’ban Panjaitan; Adis Adela Putri; Karolin Stevani Br. Barus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the differences in motivation and participation of learners in Community Learning Centers (PKBM) located in rural and urban areas, with case studies of PKBM Laskar Pelangi (village) and PKBM Al-Ikhram (city). Learning motivation in villages tends to be pragmatic and oriented toward functional skills to support family economic well-being, while motivation in cities is more directed toward improving academic qualifications and careers. Participation in rural PKBM is more intense and consistent, although quantitatively lower due to limited facilities and time. Meanwhile, participation in urban PKBM is higher quantitatively but less consistent due to limited time and busy schedules. Key supporting factors include family support, educational facilities, and program relevance, while the main constraints are economic constraints, time constraints, and facilities. This study concludes that PKBM management strategies tailored to local characteristics are necessary to increase the effectiveness of non-formal education programs.